1995
DOI: 10.1128/iai.63.10.3846-3850.1995
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of functional regions on the transferrin-binding protein (TfbA) of Actinobacillus pleuropneumoniae

Abstract: Actinobacillus pleuropneumoniae can use porcine transferrin as the sole source of iron. Two proteins with molecular masses of approximately 60 kDa (TfbA) and 110 kDa have been shown to specifically bind porcine transferrin; from the TfbA protein, three isoforms from A. pleuropneumoniae serotypes 1, 5, and 7 have been identified and characterized by nucleotide sequence analysis. Here we defined the transferrin-binding region(s) of the TfbA protein of A. pleuropneumoniae serotype 7 by TnphoA mutagenesis, random … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0
2

Year Published

1996
1996
2010
2010

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 29 publications
1
19
0
2
Order By: Relevance
“…It is interesting to note that this binding was demonstrated with a very sensitive reporter system and was not compared with the binding of host (human) Tf. The potential for loss of host-speci®c binding under certain conditions is not totally unexpected, as there are a number of TbpB peptide regions involved in binding Tf (Strutzberg et al, 1995;Renauld-Monge  nie et al, 1997), and several of these peptides have been Q 1999 Blackwell Science Ltd, Molecular Microbiology, 32, 111±121 Fig. 4.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is interesting to note that this binding was demonstrated with a very sensitive reporter system and was not compared with the binding of host (human) Tf. The potential for loss of host-speci®c binding under certain conditions is not totally unexpected, as there are a number of TbpB peptide regions involved in binding Tf (Strutzberg et al, 1995;Renauld-Monge  nie et al, 1997), and several of these peptides have been Q 1999 Blackwell Science Ltd, Molecular Microbiology, 32, 111±121 Fig. 4.…”
Section: Discussionmentioning
confidence: 99%
“…reported not to maintain the strict host speci®city of binding (Strutzberg et al, 1995). Thus, initial binding by segments of TbpB recognizing sequences/structures unique to hTf may be followed by interactions involving regions of hTf that are common to other Tfs.…”
Section: Discussionmentioning
confidence: 99%
“…The pathogen specifically binds porcine TF , and the ability to use TF-bound iron is required for virulence (Baltes et al 2002). Further, the TF receptor is highly specific , and it has been shown that the A. pleuropneumoniae serotypes 1 and 5, being most prevalent in North America, have distinct TF receptor alleles from A. pleuropneumoniae serotype 2, being most prevalent in Northern Europe (Gerlach et al 1992;Strutzberg et al 1995).…”
mentioning
confidence: 99%
“…La proteína TbpB es una lipoproteína que se encuentra expuesta en la superficie de la bacteria, siendo posible la existencia de dominios transmembrana que le permitirían extenderse hacia la membrana interna (Gerlach et al, 1992), mientras que el resto se proyectaría hacia el exterior. Los anticuerpos obtenidos a partir de animales convalecientes de la infección no reconocen el extremo N-terminal de la proteína (necesaria para que se una de forma estable a la transferrina), lo que pone de manifiesto una cierta variabilidad entre sus isoformas (Strutzberg, 1995); sin embargo, la región C-terminal está muy conservada (Gerlach et al, 1992).…”
Section: Proteínas De Membrana Externa Tbpa Y Tbpbunclassified
“…Posteriormente, se ensayaron conjugados de Apx con polisacáridos capsulares. que la región de la proteína principalmente reconocida por anticuerpos es la Cterminal, que también es la más conservada entre los diferentes serotipos(Strutzberg et al, 1995). Se ha descrito un preparado inmunógeno basado en el sobrenadante de un cultivo obtenido en condiciones de restricción de hierro, compuesto básicamente por hemolisinas y proteínas no integrales de membrana externa, entre ellas la TbpB.…”
unclassified